Pristine microstructures in pseudotachylytes formed in dry lower crust, Lofoten, Norway - Dunkel, Kristina G.; Morales, Luiz F.G.; Jamtveit, Bjørn (Royal Society, 2021)
Feldspar-rich pseudotachylytes from the island of Moskenesøya, Lofoten, formed in dry granulites under lower crustal conditions during the Caledonian orogeny. The central parts of the pseudotachylytes, where the cooling rates were slowest, are characterized by microlites and spherulites of plagioclase and K-feldspar. K-feldspar surrounding plagioclase is consistent with crystallization from a melt during cooling instead of devitrification as the origin of the spherulites. Very thin (a few micrometres wide) injection veins, which experienced very rapid quenching, contain amorphous or cryptocrystalline material. The preservation of this material and of the fine-grained microstructures shows that, under fluid-absent conditions, recrystallization and reactions are slow and the original microstructures of the pseudotachylytes can be preserved. This article is part of a discussion meeting issue 'Understanding earthquakes using the geological record'.